The Use of Technology for a Technical Analysis in Tennis - A Tribute to Gilles de Kermadec - Martin , Caroline; Pestre, Bernard; Peter, Jean-Michel (ITF Coaching & Sport Science Review, 2014)
The storage capacity of a growing number of data and images, the ability to capture 1000 frames per second and the improved speed of editing mark a new stage in the technical analysis of sporting actions. Today, just type the word “tennis” in any search engine and browse the Internet to see the many results. Due to this, it seemed useful to us to have three tennis experts; a historian, a researcher in biomechanics and a National Technical Director, to reflect on the impact of technology in the development of technical analysis and teaching.